Yield, fruit quality, and survival of 'Pêra' sweet orange on eight rootstocks in tropical cohesive soils - Carvalho, Hélio Wilson Lemos de; Carvalho, Luciana Marque de; Teodoro, Adenir Vieira; Barros, Inácio de; Girardi, Eduardo Augusto; Soares Filho, Walter dos Santos; Passos, Orlando Sampaio (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to determine the influence of eight rootstocks on the yield, fruit quality, and survival of 'Pêra CNPMF D6' sweet orange (Citrus sinensis) trees grown under rainfed conditions in a cohesive soil of the Brazilian Northeast. In 2014–2018, the yield, fruits, and survival of trees planted in 1997 were evaluated in a randomized complete block design. Yield was assessed using annual fruit production, yield efficiency, and the alternate bearing index. Tree survival was considered the percentage of plants that remained alive until 2018. Fruit quality was evaluated by physicochemical attributes. 'Cravo' confirmed its good yield performance. Despite the lower number of trees, the 'Mazoe' rough lemon rootstock induced the highest fruit yield. The 'Cravo' x 'Cleópatra' hybrid and 'Volkameriano' lemon favored the highest trees survival, whereas 'Indio' citrandarin and 'Cravo' lime resulted in intermediate levels. The 'San Diego' and 'Riverside' citrandarins induced shorter tree with a high yield efficiency and a higher alternate bearing index, respectively. Fruits with less juice and mass were induced, respectively, by 'Riverside' citrandarin and 'Volkameriano' lemon. It can be concluded that the 'Mazoe' rootstock induces a higher fruit yield and 'Cravo' x 'Cleópatra' and 'Volkameriano', a greater survival. In addition, all rootstocks, except 'Riverside' and 'Volkameriano', induce fruit that meet the minimum quality requirements.